(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Some pathogenetic risk factors (platelet-derived growth factor (PDGF); tumor necrosis factor alpha (TNF?); and Endothelin-1 (ET1)) are involved in the development of diabetic maculopathy (DMP) in type 2 diabetes mellitus. We hypothesized that the same factors are involved in the formation of postsurgical recurrent DMP. Purpose: To investigate new risk factors of postsurgical recurrent DMP in patients with DM2. Materials and Methods: The study included 313 patients with DM2 (313 eyes) and diabetic maculopathy. These included patients with mild nonproliferative diabetic retinopathy (NPDR; Group 1; n=40), moderate or severe NPDR (Group 2; n=92), and proliferative diabetic retinopathy (PDR; Group 3; n=181). Patients received one of the four types of surgical treatment: only three-port closed subtotal vitrectomy (CSTV; n=78); CSTV combined with internal limiting membrane (ILM) peeling (n=85); CSTV combined with ILM peeling and panretinal laser coagulation (PRLC) (n=81); and CSTV combined with ILM peeling, PRLC and cataract phacoemulsification (phaco) (n=69). Enzyme-linked immunosorbent assay was used to determine presurgical levels of DMP risk factors in blood. Statistical analyses were conducted using Statistica 10.0 (StatSoft, Tulsa, OK, USA) software. Results: Presurgical levels of DMP risk factors in blood substantially increased with an increase in severity of diabetic retinopathy (from Group 1 to Group 3), with the maximum values achieved in patients with PDR. For each group, PDGF blood levels in patients with recurrent DMP were 1.3- to 1.4-fold (and statistically significantly, p < 0.001) higher than in those without recurrent DMP. TNF? blood levels in Group 1 and Group 2 patients with recurrent DMP were 1.2- to 1.4-fold (and statistically significantly) higher than in those without recurrent DMP. Only for Group 1, median ET1 blood level in patients with recurrent DMP was significantly (1.4-fold; p < 0.001) higher than in those without recurrent DMP. All patients exhibiting recurrent DMP after any of the used surgical treatment technologies had statistically significantly increased baseline PDGF levels (p < 0.001). The pre-surgery cut-off PDGF blood level for which the development of recurrent DMP becomes probable was > 51.8 ng/mL. Associations of TNF? and ЕТ1 blood levels with recurrent DMP were most prominent in NPDR, and depended on recurrence time points: presurgical TNF? blood levels were associated with early recurrent DMP, whereas presurgical ЕТ1 blood levels were associated with late recurrent DMP. Conclusion: New risk factors for post-surgical recurrent DMP in DM2 were established. The PDGF blood level was found to influence the development of both early and late recurrent DMP, whereas the TNF? blood level, only early SMP recurrence, and the ET1 blood level, only late recurrent DMP.